Generalized Contractions on Extended \(b\)-Metric Space Endowed With a Graph - Kumar, Neeraj; Mehra, Seema (Communications in Mathematics and Applications, 2022)
The goal of this study is to obtain fixed point and coincidence point results for interpolative Hardy Rogers and Ćirić-Reich-Rus type contractive type mappings in an extended $b$-metric space, which is a generalization of \(b\)-metric space, based on Errai et al. (Some new results of interpolative Hardy-Rogers and Ćirić-Reich-Rus type contraction, 2021 (2021), Article ID 9992783). We present a variety of examples which backs up our findings.
Keywords: Contraction; Fixed point; Extended b-metric space; Graph